Musicians' Mobilities and Music Migrations in Early Modern Europe: Biographical Patterns and Cultural Exchanges - Nieden, Gesa zur (2016)
During the 17th and 18th century musicians' mobilities and migrations are essential for the European music history and the cultural exchange of music. Adopting viewpoints that reflect different methodological approaches and diversified research cultures, the book presents studies on central scopes, strategies and artistic outcomes of mobile and migratory musicians as well as on the transfer of music. By looking at elite and non-elite musicians and their everyday mobilities to major and minor centers of music production and practice, new biographical patterns and new stylistic paradigms in the European East, West and South emerge.